(untitled) (Universal International Scientific Journal, 2026)
This thesis analyzes didactic and organizational ways to improve the effectiveness of teaching network-technical subjects based on a simulation learning environment. The goal is to enrich competency-oriented laboratory activities with virtual models. The methodology uses pedagogical experiment, comparison, and learning analytics approaches. The novelty lies in the proposal of an integrated model of simulation scenarios and assessment rubrics.